2005
DOI: 10.1017/s0266467405002476
|View full text |Cite
|
Sign up to set email alerts
|

Common allometric equations for estimating the tree weight of mangroves

Abstract: Inventory data on tree weights of 104 individual trees representing 10 mangrove species were collected from mangrove forests in South-East Asia to establish common allometric equations for the trunk, leaf, above-ground and root weight. We used the measurable tree dimensions, such as dbh (trunk diameter at breast height), DR0.3 (trunk diameter at 30 cm above the highest prop root of Rhizophora species), DB (trunk diameter at lowest living branch), and H (tree height) for the independent variable of equations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
282
0
34

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(365 citation statements)
references
References 22 publications
9
282
0
34
Order By: Relevance
“….information (if any) about carbon losses associated to clear-falling are [sic] difficult to obtain since this activity is illegal in most countries; actual records of total biomass extracted to use mangrove area for other purposes (e.g., roads, urban development) is also rare making it difficult to determine this component in global estimates of carbon sequestration." In order to account for the impact of selective logging on biomass and carbon reservoirs in the vicinity of the Turbo municipality, we combined forest structure data [39] and published allometric equations [58,59]. Fringing mangroves at the Atrato River Delta stored the greatest amount of aboveground carbon (89.3 Mg C/ha) in comparison to the Eastern Coast mangroves ( Table 2).…”
Section: Estimated Biomass and Carbon Reservoirs As Influenced By Defmentioning
confidence: 99%
“….information (if any) about carbon losses associated to clear-falling are [sic] difficult to obtain since this activity is illegal in most countries; actual records of total biomass extracted to use mangrove area for other purposes (e.g., roads, urban development) is also rare making it difficult to determine this component in global estimates of carbon sequestration." In order to account for the impact of selective logging on biomass and carbon reservoirs in the vicinity of the Turbo municipality, we combined forest structure data [39] and published allometric equations [58,59]. Fringing mangroves at the Atrato River Delta stored the greatest amount of aboveground carbon (89.3 Mg C/ha) in comparison to the Eastern Coast mangroves ( Table 2).…”
Section: Estimated Biomass and Carbon Reservoirs As Influenced By Defmentioning
confidence: 99%
“…Within sample plot (100×50 m), all tree heights and diameters were measured. The Diameter (D) of trees was measured using diameter tape at 30 cm above the highest prop-roots while tree Height (H) was measured using hypsometer (Komiyama et al, 2005). To estimate the aboveground tree biomass in this forest, seven tree samples were selected for sampling (2 small, 3 medium and 2 big size trees).…”
Section: Study Sitementioning
confidence: 99%
“…Therefore, attention has been paid to develop techniques to estimate tree biomass from easily measured tree characteristics known as 'allometry'. Allometry is a powerful tool for estimating biomass production from easily measured tree characteristic such as stem diameter and height that are quantifiable in the field (Komiyama et al, 2005). Common allometric equations have been reported for aboveground biomass (Brown et al, 1989;Brown, 1997;Ketterings et al, 2001) and also for mangroves biomass (Komiyama et al, 2002;Ong et al, 2004;Nguyen and Ninomiya, 2007) elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The study confirmed the importance of the red-edge band of WV2 satellite image and associated vegetation indices for AGB estimation over other spectral regions. Komiyama et al [19], Komiyama et al [5], Fu and Wu [4] and Perera and Amarasinghe [20] derived only a relationship between mangrove canopy dynamics, AGB and vegetation indices. Therefore, testing the possibility of mapping AGB of mangroves over a large area from remotely-sensed data is still required.…”
Section: Introductionmentioning
confidence: 98%